Quantitative analysis of bone morphogenetic protein 15 (BMP15) and growth differentiation factor 9 (GDF9) gene expression in calf and adult bovine ovaries - Hayashi Ken-go; Ushizawa Koichi; Kaneyama Kanako; Hosoe Misa; Takahashi Toru (BMC, 2011)
Abstract Background It has been reported that calf oocytes are less developmentally competent than oocytes obtained from adult cows. Bone morphogenetic protein 15 (BMP15) and growth and differentiation factor 9 (GDF9) play critical roles in folliculogenesis, follicular development and ovulation in mammalian ovaries. In the present study, we attempted to compare the expression patterns of BMP15 and GDF9 in the cells of calf and cow ovaries to determine a relationship between the level of these genes and the low developmental competence of calf oocytes. Methods Bovine tissues were collected from 9-11 months-old calves and from 4-6 years-old cows. We characterized the gene expression of BMP15 and GDF9 in calf and adult bovine oocytes and cumulus cells using quantitative real-time reverse transcriptase polymerase chain reaction (QPCR) and in situ hybridization. Immunohistochemical analysis was also performed. Results The expression of BMP15 and GDF9 in cumulus cells of adult ovaries was significantly higher than that in calf ovaries, as revealed by QPCR. GDF9 expression in the oocytes of calf ovaries was significantly higher than in those of the adult ovaries. In contrast, BMP15 expression in the oocytes of calf and adult ovaries was not significantly different. The localization of gene expression and protein were ascertained by histochemistry. Conclusions Our result showed for the first time BMP15 and GDF9 expression in bovine cumulus cells. BMP15 and GDF9 mRNA expression in oocytes and cumulus cells was different in calves and cows.